Four new species and some new records of Brazilian frog-biting midges (Diptera: Corethrellidae) - Amaral, André P.; Mariano, Rodolfo; Pinho, Luiz Carlos (Zootaxa, 2019)
Four new species of Corethrella are described from Brazil. Corethrella xokleng sp. n. and C. cambirela sp. n. are described from males and females, and Corethrella yanomami sp. n. and C. munteantaroku sp. n. are described from a female and male, respectively. Fourteen Corethrella species have new distributional records, with five of these being first records for Brazil. The number of valid species of Corethrellidae known from Brazil is increased from 37 to 46.